Pluviosidade crítica e aspectos agravantes de deslizamentos nas encostas da Cidade do Rio de Janeiro - período de 1998 a 2002 - Luiz, Bruna Julianelli (2017)
Analyzes the effects of rainfall in the landslides in the city of Rio de Janeiro for the years of 1998 to 2002 and the results compared to those from the years of 2010 to 2012. These results show that the rainfall events are the predominant cause of landslides; however, they are not the only triggering factor. In addition to that, a higher number of occurrences, for the period of 1998 to 2002, occurred in areas with human interventions than in areas without these interventions. Furthermore, the results also show that the number of occurrences is higher in areas with low-income communities than in other areas of the city. The analyses was made considering the product of the hourly rainfall intensity and accumulated rainfall for 96h, simultaneously, showing that the different regions in Rio de Janeiro do not have the same behavior. Additional analysis, considering the product of the hourly rainfall intensity and accumulated rainfall, IAn , made possible to verify its correlation with the number of occurrences of landslides per km2 of area susceptible to landslide. Moreover, the results also show that some regions of the city present a significantly differences susceptibility to landslide due to rainfall compared to the average behavior of the city due to their different geology, occupancy and human intervention.